2004
DOI: 10.1177/008124630403400103
|View full text |Cite
|
Sign up to set email alerts
|

Rites of Passage: Identity and the Training of Clinical Psychologists in the Current South African Context

Abstract: This article attempts to make sense of the clinical psychology training experience, as a negotiation of personal and professional identity. It suggests that the training, particularly in the first year, is a rite of passage, in many respects similar to an initiation process. Rites of passage can be seen as processes marking shifts in status and social identity. In the case of training to be a psychologist this change involves the movement from lay to professional status. There are three phases involved in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…Skovholt e Ronnestad (1995), inspirados por Erikson (1968) e Marcia (1966 afirmam que o desenvolvimento se processa através de momentos de exploração, reflexão e abertura, nos quais o Psicoterapeuta poderá usufruir de moratórias; e que a estagnação se relaciona com uma defensividade e um enclausuramento prematuro cujo fito é diminuir a ansiedade, mas que resultará ora num pseudo-desenvolvimento, ora num abandono da profissão. Na verdade, vários autores fazem referência à construção da identidade profissional associada ao DP e a esta fase desenvolvimental que corresponde à adaptação à transição de papéis, dada a incongruência entre o self pessoal e o self exigido no contexto profissional de estágio, nomeadamente (Ducheny et al, 1997;Elman, Illfelder-Kaye, & William, 2005;Fouad, 2003;Ibarra, 1999Ibarra, , 2003Ibarra & Barbulescu, 2010;Kottler & Swartz, 2004).…”
Section: Tornar-se Psicólogo No Final Da Formação Académica: Modelos unclassified
“…Skovholt e Ronnestad (1995), inspirados por Erikson (1968) e Marcia (1966 afirmam que o desenvolvimento se processa através de momentos de exploração, reflexão e abertura, nos quais o Psicoterapeuta poderá usufruir de moratórias; e que a estagnação se relaciona com uma defensividade e um enclausuramento prematuro cujo fito é diminuir a ansiedade, mas que resultará ora num pseudo-desenvolvimento, ora num abandono da profissão. Na verdade, vários autores fazem referência à construção da identidade profissional associada ao DP e a esta fase desenvolvimental que corresponde à adaptação à transição de papéis, dada a incongruência entre o self pessoal e o self exigido no contexto profissional de estágio, nomeadamente (Ducheny et al, 1997;Elman, Illfelder-Kaye, & William, 2005;Fouad, 2003;Ibarra, 1999Ibarra, , 2003Ibarra & Barbulescu, 2010;Kottler & Swartz, 2004).…”
Section: Tornar-se Psicólogo No Final Da Formação Académica: Modelos unclassified
“…Much has been written about the personal effect of training as a psychotherapist and, more specifically, about the negative aspects (Kottler & Swartz, 2004;Truell, 2001). However, almost two decades ago, Blocher (1987) already argued that the extent to which training programmes were growth-promoting was a critical aspect of professional training.…”
Section: Comparing My Mood During the Workhop With My Mood In Other mentioning
confidence: 99%
“…Therefore, a positive group experience in professional training, as elicited by a positive psychology stance, could be conducive to students' well-being. Kottler and Swartz (2004) have described the class as a community where students are supported in developing their professional identity. In this sense, it seemed that a focus on positive psychological constructs has contributed to the experience of a positive sense of community and has thereby enhanced the development of the professional identity of these students.…”
Section: Theme 4: Positive Effect On Group Dynamics and Sense Of Commmentioning
confidence: 99%
See 1 more Smart Citation
“…Master's students in psychology are a unique population, in that they have to deal with academic stressors and demands as well as take on the new role of being a psychologist. It has been shown that high stress levels can affect both clinical practice and the overall training experience (Elman & Forrest, 2007;Gaubatz & Vera, 2006;Kottler & Swartz, 2004;Myers et al, 2012;Rønnestad & Skovholt, 2003;Rosenberg, Getzelman, Arcinue, & Oren, 2005). The majority of these negative experiences can be explained by the possibility that a student's psychological issues may be uncovered by studying to practise psychotherapy, by exposure to methods of self-analysis, and by balancing student roles with professional roles (Barnett & Hyde, 2001;Dearing, Maddux, & Tangney, 2005;Holzman, Searight, & Hughes, 1996;Howard, Inman, & Altman, 2006;Pillay & Kritzinger, 2007;Stratton, Kellaway, & Rottini, 2007;Truell, 2001).…”
Section: Introductionmentioning
confidence: 99%